2008
DOI: 10.4161/cc.7.24.7398
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected link between anaphase promoting complex and the toxicity of expanded polyglutamines expressed in yeast

Abstract: Protein aggregation is intimately linked to a number of neurodegenerative diseases. Expansion of the huntingtin polyglutamine-rich domain causes protein aggregation and neuronal degeneration. Recently we found that, similar to neurons, yeast expressing the expanded domain show markers of programmed cell death. Here we showed that deletion of yeast metacaspase gene YCA1 partly rescues the toxic effect of the domain overexpression. We also performed genetic screen for other genes deletions alleviating the toxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Despite its established role in the exit from mitosis it has been shown that the APC is functional in post-mitotic neurons (Gieffers et al 1999; Kim et al 2009; Marrocco et al 2009) with a role in cognitive processes (Kuczera et al 2011). Further evidence suggests that deregulated APC function are associated with neurodegeneration and cognitive decline (Almeida et al 2005; Li et al 2008; Maestre et al 2008) and a screen in yeast identified the APC as modifier of polyQ toxicity (Bocharova et al 2008). Considering existing evidence, we propose that these APC components represent novel proteostasis modifiers with a role in degradation through their E3 ubiquitin ligase function, while mechanistically it is possible that they may function as co-chaperones.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its established role in the exit from mitosis it has been shown that the APC is functional in post-mitotic neurons (Gieffers et al 1999; Kim et al 2009; Marrocco et al 2009) with a role in cognitive processes (Kuczera et al 2011). Further evidence suggests that deregulated APC function are associated with neurodegeneration and cognitive decline (Almeida et al 2005; Li et al 2008; Maestre et al 2008) and a screen in yeast identified the APC as modifier of polyQ toxicity (Bocharova et al 2008). Considering existing evidence, we propose that these APC components represent novel proteostasis modifiers with a role in degradation through their E3 ubiquitin ligase function, while mechanistically it is possible that they may function as co-chaperones.…”
Section: Discussionmentioning
confidence: 99%
“…These include an apoptotic phenotype and nuclear polyglutamine aggregation, both of which are caspase-dependent (Sokolov et al, 2006; Bocharova et al, 2008). It is very tempting to speculate whether yeast cells also possess a conserved pqn-41 -like polyglutamine protein, the expression of which might elicit an alternative caspase-independent PCD pathway that is similar or identical to linker cell death in C. elegans .…”
Section: Discussionmentioning
confidence: 99%
“…PolyQ expression (103Q but not 103QP) also induced ER stress leading to UPR (Duennwald and Lindquist, 2008), and has also been proposed to lead to lethal impairment of cell cycle progression (Bocharova et al, 2008, 2009). ER and cell cycle impairments are believed to be consequences of the impairment of specific branches of the UPS pathway by polyQ expression (103Q), including the ERAD and anaphase promoting complex (APC) pathways (Bocharova et al, 2008, 2009; Duennwald and Lindquist, 2008). The mitochondrion-associated protein degradation pathway (MAD) shares pivotal components with the ERAD pathway (Heo et al, 2010; Taylor and Rutter, 2011).…”
Section: Yeast Models Expressing Neurotoxic Proteinsmentioning
confidence: 99%
“…These data are in line with the idea that ERAD dysfunction by polyQ expression (103Q) is critical in the execution of cytotoxicity and cell death. Deletion of the APC substrate ASE1 relieved polyQ-triggered cytotoxicity (103Q), suggesting that preventing the accumulation of Ase1 upon dysfunction of the APC pathway is beneficial (Bocharova et al, 2008). Expression of polyQ flanked by the proline-rich domain (96QP), which is non-toxic under normal conditions, became cytotoxic upon accumulation of the UPS model substrate ΔssCPY * and could be relieved upon Sis1 overexpression (Park et al, 2013).…”
Section: Yeast Models Expressing Neurotoxic Proteinsmentioning
confidence: 99%